(untitled) (Stamford Journal of Microbiology, 2013)
The aim of the present study was the isolation and identification of bacteria from trachea and lung of slaughtered buffaloes. A total of 160 swab samples were collected from tracheas (80) and lungs (80) freshly slaughtered buffeloes from the slaughter houses of Dinajpur Sadar, Dinajpur, Bangladesh, during the period from June 2011 to February 2012. Among them, 9 tracheas (out of 80 samples) and 30 lungs (out of 80 samples) showed visible lesions. Bacterial isolates were identified based on their growth, morphological and biochemical characteristics. The most frequent (5%) bacterial isolate in tracheas was Staphylococcus spp. Pasteurella haemolytica and Staphylococcus spp. were isolated from different types of lung lesions in a frequency of 5% and 16.25%, respectively. P. haemolytica showed ?- haemolysis on blood agar and did not ferment lactose and dulcitol whereas dextrose, manitol and maltose were fermented with the production of acid. This investigation would be helpful for veterinarian for the detection, treatment and control of tracheal and lung diseases of buffaloes. DOI: http://dx.doi.org/10.3329/sjm.v2i1.15211 Stamford Journal of Microbiology, Vol.2(1) 2012: 31-33